THE EFFECT OF BALL RELAY GAMES ON LEARNING OUTCOMES IN THE 60-METER SPRINT AMONG 7TH-GRADE STUDENTS IN CLASS A AT SIPISPIS PUBLIC JUNIOR HIGH SCHOOL 2 - Dirga purba DIRGA; Abdul Harris Handoko; Usman Nasution (Journal of Physical Education, Health and Sports Recreation, 2026)
This study aims to determine the effect of a ball relay game on learning outcomes in the 60-meter sprint among seventh-grade A students at Sipispis State Elementary School 2. The research method used was a quantitative experiment with a quasi-experimental design. The sample consisted of 30 seventh-grade A students selected using purposive sampling. Data collection was conducted through a pre-test and a post-test. The results of the data analysis showed a significance value (two-tailed) of 0.000 < 0.05, which means that H0 was rejected and H1 was accepted. It can be concluded that there is a significant difference between learning outcomes before and after the intervention, indicating that the ball relay game has a significant effect on improving learning outcomes in the 60-meter sprint.